Pathological findings in a Dachshund-cross dog with neuroaxonal dystrophy. Issue 1 (December 2015) - Pintus, Davide; Cancedda, Maria; Macciocu, Simona; Contu, Claudia; Ligios, Ciriaco
Abstract Background Neuroaxonal dystrophy (NAD) is a neurodegenerative condition affecting humans and animals characterized by the widespread presence of swollen axons (spheroids). Case presentation Herein, we report the pathological findings in a case of neuroaxonal dystrophy in a Dachshund-cross puppy, which was euthanized because of a proprioceptive positioning deficits and irreversible ataxia of the hind limbs. Histologically, there was a bilaterally symmetric neuroaxonal dystrophy with eosinophilic axonal spheroids exclusively localized at the level of the ventral posterior lateral nucleus of the thalamus, medial lemniscus, gracilis nucleus, medial cuneatus nucleus in the brain as well as the gracilis and cuneatus fasciculi throughout the spinal cord. Conclusion To the authors' knowledge, this is the first report of canine neuroaxonal dystrophy with this exclusive and specific localization only in the neuronal circuit implicated in the transmission of conscious proprioceptive information.